(untitled) - Langan, John (New York, 1987)
Intended for courses in developmental writing, SENTENCE SKILLS, Fifth Edition, Form B, is the alternate version of the Fifth Edition, Form A, which is known for its especially effective instruction on grammar, mechanics, punctuation, and usage rules needed for clear writing. Clear, readable explanations and an abundance of practice and editing and proofreading tests characterize SENTENCE SKILLS. With the Fifth Edition comes a convenient Annotated Instructor's Edition, as well as refinements to the worktext -- with expanded practice in writing simple paragraphs and essays in Part Four, "Writing Assignments." The alternate forms provide different exercises and examples, but offer the same basic instruction. Thus, if instructors want to use different books from one semester to the next, or from one class to the next, they can do so with full ease, as minimal syllabus adjustment is required
Keywords: English language,English language,Tiếng anh; Sentences,Problems, exercises, etc.,Grammar,Problems, exercises, etc.,Những vấn đề, bài tập,Câu